Sources and causes of water pollution in Bangladesh: A technical overview - Arefin, Md. Arman; Mallik, Avijit (BIBECHANA, 2017)
Water pollution is one of the significant dangers to general wellbeing in Bangladesh. Drinking water quality is inadequately overseen and checked. Bangladesh positions at number 86 among 142 countries with respect to drinking water quality. Drinking water sources, both surface and groundwater are debased with coliforms, harmful metals and pesticides all through the nation. Different drinking water quality parameters set by WHO are every now and again damaged. Human exercises like uncalled for transfer of civil and mechanical effluents and aimless utilizations of agrochemicals in agribusiness are the principle factors adding to the crumbling of water quality. Microbial and substance contaminations are the primary elements mindful solely or in mix for different general medical issues. This paper presents a detailed layout of water quality in Bangladesh with unique accentuation on significant poisons, sources and causes of pollution. The information introduced in this paper are extracted from different surveys and reports distributed in national and global journals. Likewise reports discharged by the government and NGO associations are incorporated. BIBECHANA 15 (2018) 97-112